Nursing as a political posture for the implementation of social justice - Gutiérrez Velázquez, Ana Sofía (2023)
Social justice is not exclusive to nursing, since by providing care the integrity of the patient is being safeguarded by going beyond the sick person, since through this, the establishment of more equitable forms of power is made possible. Nursing is a participant in the experience of human health care; but for this to transcend, you must avoid imposing norms, standards and rules, being more of an observer than an active element in the self-care experience and respecting the autonomy of the subject of care. Thus, by transforming the perspective of their self-care, nursing will be able to generate a real impact at a social level.